2015
DOI: 10.5943/cream/5/3/5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Gasteroid Fungi (Basidiomycota) in Hollongapar Gibbon Wildlife Sanctuary, Jorhat, Assam, India

Abstract: Hollongapar Gibbon Wildlife Sanctuary (HGWLS), Jorhat, Assam is mainly famous for Hollock Gibbon and other six primate species found in the sanctuary. A total of 22 gasteroid fungal species belongs to 9 genera, 4 families, 4 orders, 2 sub-classes and 1 class, have been found in the study site. The family Agaricaceae (8 spp.) is highly dominant in the study site followed by Phallaceae (7 spp.), Geastraceae (4 spp.), and Sclerodermataceae (3 spp.). The name of the gasteroid fungi species along with their occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Northeastern India (a part of Indo Burma) is a biodiversity hotspot (Myers et al 2000) of the world, a few number of wild macrofungi have been reported from this part by Gogoi & Parkash (2015a, 2015b, 2014, Khaund & Joshi (2013), Tanti et al (2011), Boruah et al (1997, and Sing & Sing (1993). A checklist is very important in order to know the distribution of a particular fungal species in different regions of a country or a state.…”
mentioning
confidence: 99%
“…Northeastern India (a part of Indo Burma) is a biodiversity hotspot (Myers et al 2000) of the world, a few number of wild macrofungi have been reported from this part by Gogoi & Parkash (2015a, 2015b, 2014, Khaund & Joshi (2013), Tanti et al (2011), Boruah et al (1997, and Sing & Sing (1993). A checklist is very important in order to know the distribution of a particular fungal species in different regions of a country or a state.…”
mentioning
confidence: 99%
“…3B shows the color of sulfur after the treatment, where the percentage of hydrocarbons is reduced to ≤ %0.015 by weight. The great difference between the color of raw and pure sulfur enabled us to adopt the color as a rapid criterion of purity, using the Methuen color system [11]. It is noteworthy that the removal of bitumen was achieved by several metal salts and was not restricted to a single definite salt [20], although, the removal efficiency and the treatment conditions varied from one definite salt to another.…”
Section: Resultsmentioning
confidence: 99%
“…The only defect of this method was the fainted copper color that can be symbolized with 3A4 on the Methuen color scale [11], although the color problem can be treated by raising the treatment temperature of sulfur to 400 C˚ according to the first patent [7]. This fact was confirmed again by another study conducted by Aldobouni et al [12] and Yin et al [13].which clarified the connection between the applied temperature and the remaining hydrocarbon in the crude sulfur with the quantity of liberated H 2 S gas (that indicates the speed of reaction), and the resulting color.…”
Section: Introductionmentioning
confidence: 99%
“…Tapwal et al (2013 reported 30 macrofungal species from six different sites in wet evergreen tropical forest of Assam. Gogoi & Parkash (2014, 2015a reported wild macrofungi from Assam. Debnath et al (2020) reported 217 macrofungi from different districts of Tripura.…”
Section: Introductionmentioning
confidence: 99%